Percutaneous closure of patent foramen ovale in migraine with aura, a randomized controlled trial. (22nd February 2016) - Mattle, Heinrich P.; Evers, Stefan; Hildick-Smith, David; Becker, Werner J.; Baumgartner, Helmut; Chataway, Jeremy; Gawel, Marek; Göbel, Hartmut; Heinze, Axel; Horlick, Eric; Malik, Iqbal; Ray, Simon; et al.
Abstract: Aims: Migraine with aura and patent foramen ovale (PFO) are associated. The Percutaneous Closure of PFO in Migraine with Aura (PRIMA) trial is a multicentre, randomized trial to investigate the effect of percutaneous PFO closure in patients refractory to medical treatment. Methods: Migraine with aura patients and PFO who were unresponsive to preventive medications were randomized to PFO closure or medical treatment. Both groups were given acetylsalicylic acid 75–100 mg/day for 6 months and clopidogrel 75 mg/day for 3 months. The primary endpoint was reduction in monthly migraine days during months 9–12 after randomization compared with a 3-month baseline phase before randomization. The committee reviewing the headache diaries were blinded to treatment assignment. Results: One hundred and seven patients were randomly allocated to treatment with an Amplatzer PFO Occluder ( N = 53) or control with medical management ( N = 54). The trial was terminated prematurely because of slow enrolment. Eighty-three patients (40 occluder, 43 control) completed 12-month follow-up. Mean migraine days at baseline were 8 (±4.7 SD) in the closure group and 8.3 (±2.4) in controls. The primary endpoint was negative with −2.9 days after PFO closure vs. −1.7 days in control group ( P = 0.17). Patent foramen ovale closure caused five adverse events without permanent sequelae. Conclusion: In patients with refractory migraine with aura and PFO, PFO closure did not reduce overall monthly migraine days.